2019
DOI: 10.18502/npt.v6i3.1258
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adaptability and life satisfaction among ostomy patients

Abstract: Background & Aim: Ostomy surgery is used to provide a means of collecting waste through a channel. However, ostomy can produce functional problems and major changes in adaptability and life satisfaction among the patients. This study attempts to investigate the relationship between adaptability and life satisfaction among ostomy patients. Methods & Materials: This study is descriptive-correlational. 100 ostomy patients referring to Iran Ostomy Association were selected and studied using continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In their systematic review, Recalla and colleagues14 observed that people living with an ostomy required specialized care and management to maintain their physical health and HRQOL. Additional constitutional factors also contribute to adjustment to life with an ostomy such as a secure financial status, employment, insurance coverage, WOC/Ostomy nurse availability, meeting with a person living with an ostomy after stoma surgery or ostomy support group participation, and learning to prevent or promptly manage stoma and peristomal complications 12,15–18. Given the potential for information technologies to enhance ostomy self-management, identify stomal or peristomal skin complications, and enhance psychosocial adjustment to an ostomy1,15–17, this systematic literature aimed to identify different types of health information technologies that have been applied to ostomy management and identify their influence on improving ostomy management.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their systematic review, Recalla and colleagues14 observed that people living with an ostomy required specialized care and management to maintain their physical health and HRQOL. Additional constitutional factors also contribute to adjustment to life with an ostomy such as a secure financial status, employment, insurance coverage, WOC/Ostomy nurse availability, meeting with a person living with an ostomy after stoma surgery or ostomy support group participation, and learning to prevent or promptly manage stoma and peristomal complications 12,15–18. Given the potential for information technologies to enhance ostomy self-management, identify stomal or peristomal skin complications, and enhance psychosocial adjustment to an ostomy1,15–17, this systematic literature aimed to identify different types of health information technologies that have been applied to ostomy management and identify their influence on improving ostomy management.…”
Section: Introductionmentioning
confidence: 99%
“…10 Although creation of an ostomy is essential in the management of multiple medical conditions, living with an ostomy creates a wide range of physical, social, and psychological challenges influencing social reactions, job considerations, and activities of daily living. 11,12 Living with an ostomy may diminish HRQOL in multiple areas including vitality, physical and social life, and travel. 12,13 Fortunately, these challenges tend to diminish over time as the individual adjusts to a new normal that includes caring for his or her ostomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found in the studies that 30-59% of patients with stoma could not perform at least one preoperative activity in the postoperative period, experience problems in meeting new people, are less involved in entertainment activities, used public transportation less, and had problems with intimacy with the opposite sex 7,8 . The problems experienced by patients with stoma negatively affect the quality of life especially in the postoperative first weeks.…”
Section: Introductionmentioning
confidence: 99%